Highlight article: Dysfunctional Cav1.2 channel in Timothy syndrome, from cell to bedside. Issue 12 (September 2019) - Han, Dan; Xue, Xiaolin; Yan, Yang; Li, Guoliang
Timothy syndrome is a rare disorder caused by CACNA1C gene mutations and characterized by multi-organ system dysfunctions, including ventricular arrhythmias, syndactyly, dysmorphic facial features, intermittent hypoglycemia, immunodeficiency, developmental delay, and autism. Because of the low morbidity and high mortality at a young age, it remains a huge challenge to establish a diagnosis and treatment system to manage Timothy syndrome patients. Here, we aim to provide a detailed review of Timothy syndrome, discuss the mechanisms underlying dysfunctional Cav1.2 due to CACNA1C mutations, and provide some new emerging evidences in treating Timothy syndrome from cell to bedside, promoting the management of this rare disease. Impact statement: The knowledge of Timothy syndrome (TS) caused by dysfunctional Cav1.2 channel due to CACNA1C mutations is rapidly evolving as novel technologies of electrophysiology are introduced and our understanding of the mechanisms of TS develops. In this review, we focus on the TS-related dysfunctional Cav1.2 and the underlying mechanisms. We update TS-related CACNA1C mutations in a precise way over the past 20 years and summarize all reported TS patients based on their clinical presentations and molecular mechanisms, respectively. We hope this review will provide a new comprehensive way to better understand the electrophysiological mechanisms underlying TS from cell to bedside, promoting the management of TS in practice.